PCS-7 Lead Detection in Blood and Liver of Cattle sold in the Traditional Market of Denpasar City - I Ketut Berata; Ni Nyoman Werdi Susari; I Wayan Sudira; I Made Kardena (Hemera Zoa, 2018)
Lead contamination in many foods is reported to endanger consumers' health. Beef as one of the food of animal origin can be contaminated by lead mainly due to the maintenance of cattle in contaminated areas. Balinese cattle that are kept in urban landfills are reported to be contaminated with high levels of lead in the blood and in other tissues with lower levels [4]. The threat of human health from eating foods that contain leads can cause anemia because leads can substitute iron in hemoglobin [2]. Lead poisoning can also cause malfunction of various organs such as liver, kidney [1], lungs, spleen [7] and brain [9] in the form of cognitive impairment [5]. The high threat due to contamination of leads to health, then the meat health check should also be made on the presence of leads. One of the inspection efforts on the presence of lead contamination in beef, then the place of sale in the traditional market is a good location for sampling examination.